PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DI KELAS I SDN 35 SUNGAI LIMAU - suharni suharni (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Abstract This study aims to describe and obtain information about to describe and obtain information about efforts to improve student learning outcomes in the subjects of Bahasa Indonesia through cooperative learning type model of talking stick in Class I SDN 35 Sungai Limau. This research is a classroom action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 6 students of Class I SDN 35 Sungai Limau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the cooperative learning model type of talking stick can improve student learning outcomes in Indonesian subjects in SDN 35 Sungai Limau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 69.55 (enough) increased to 84.09 (good) with an increase of 14.55. Keywords: Learning Outcomes, Indonesian Learning, Cooperative Learning Model Talking Stick Type